Estudio ultraestructural en testículo de hamster vasectomizado (Mesocricetus auratus) - Ureña, Francisco (1980)
The ultrastructure of adult hamster (Mesocricetus auratus) testis was studied by means of light and electron microscopes during fourteen months after bilateral vasectomy. In all the vasectomized animals there was marked degeneration of the seminiferous tubules as well as reduction of spermatogenesis. The thickening of the basal membrane was quite evident and showed extensive infolding. In the Sertoli cells, the presence of spherical or oval membrane-bound granules, vacuoles and degenerating cytoplasmic organelles were observed in the vasectomized group. Degenerative changes of sub-cellular organelles were quite evident in the process of spermatogenesis and spermiogenesis. The number of spermatogonia, spermatocytes, spermatids and mature sperms were considerably reduced; in some cases, almost completely degenerated. Only one type of spermatogonia (Type A) remained intact in the germinal epithelium. Large numbers of multi-nucleate spermatids were observed eight months after vasectomy. These cells were identifiable at all stages of spermatogenesis but were readily detected in cap phase spermatids. There was no evidence of any regeneration occurring in the seminiferous tubules examined eight months after vasectomy.